Exergaming simulator for athletes` training and exercise testing - Nurkkala, V. -M.; Kalermo, J.; Ohtonen, O.; Hakkarainen, A.; Linnamo, V. (Sciene and nordic skiing III, 2016)
Digitalization is reaching into nearly every aspect of life. New technologies and applications are introduced to markets in an increasing speed. Virtual reality and augmented reality are facing a transition towards being accepted by a wider audience. However, for example virtual environments have rarely been applied to athletes` training and exercise testing (see e.g. Swar6n et al. 2012). Along with the proliferation of technologies, new terms and concepts are presented. The term exergaming has become widely used. The most common definition of exergame is "video games that require physical activity in order to Play" (Oh & Young, 2010). In this paper the term exergame is defined as a video game solution which inspires and motivates people to exercise by taking advantage of different technologies. In 2013-2014 the Kajaani University of Applied Sciences, in collaboration with the University of Jyväskylä and the University of Oulu, developed an exergaming simulator that connects exercise and rehabilitation equipment with virtual environments, games, immersive view and advanced motion control. The aim of the development was to bring motivation and enjoyment into training and also provide new tools for athletes` training and exercise testing. (Nurkkala et. al., 2014). The exergaming system was piloted at the Vuokatti Test Center in June 2014 for athlete training and exercise testing purposes. The infrastructure included a needed large treadmill and an intelligent coaching system called Coachtech which is explained in more detail by Ohtonen et al. in this book. The near future goal is to integrate the exergaming set up with the Coachtech system.